Kajian Prediksi 3-Dimensi Biomarker Kanker Payudara Dari Jalur Ekspresi LincRNA-ROR/MIR-145/ARF6 [3D Prediction of Breast Cancer Biomarker from The Expression Pathway of LincRNA-ROR/MIR-145/ARF6] - Parikesit, Arli Aditya; Anurogo, Dito (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2018)
According to WHO, breast cancer is one of the main causes of mortality in women. To overcome this malady, molecular biomedical research is carried out intensively. Anomalies in the lincRNA-RoR/miR-145/ARF6 expression pathway were found to play a very important role in breast cancer, especially in the type of Triple-Negative Breast Cancer (TNBC), which is the most dangerous variant of the deadly disease. Bioinformatics research has found the existence of non-coding RNA (ncRNA) in these expression pathways, whose interactions are worth studying with 3-dimensional prediction methods. The 3-D prediction method for biomolecules has been widely developed and has been successfully applied to DNA and protein. However, for the structure of RNA, it has just been developed, due to its low stability and very high dynamics on the biomolecule. Our aim is to apply the latest computational method for predicting the 3-dimensional structure of ncRNA, which can be applied as key information in biomedical application research. Extrapolation of kinetics and thermodynamic indicators of ncRNA ultimately yields the siRNA Linc-ROR 3-Dimensional structure and siRNA mRNA-ARF6, each having 13 and 8 hydrogen bonds. The existence of these hydrogen bonds is very important in maintaining the stability of the compounds and shows its efficacy as drug candidates. It is expected that preliminary information from the predicted 3-dimensional structure of ncRNA is useful for optimization of laboratory experiments in the field of crystallographic biomolecules.